IMPROVING MANAGED SECURITY SERVICE ADOPTION THROUGH GO-TO-MARKET STRATEGY TRANSFORMATION: A CASE STUDY OF SQURA CYBERSEC - Imam Rizky Hambali; Utomo Sarjono Putro (CV. Radja Publika, 2026)
Indonesia’s cybersecurity industry continues to experience rapid growth driven by digital transformation, cloud adoption, increasing cyber threats, and stronger cybersecurity regulations. However, cybersecurity providers continue to face challenges in accelerating Managed Security Service Provider (MSSP) adoption and achieving sustainable recurring revenue growth. This study aims to analyze the internal and external factors influencing MSSP adoption and formulate strategic recommendations to improve the cybersecurity Go-To-Market (GTM) strategy of SQURA Cybersec at PT Aplikanusa Lintasarta. A qualitative case study approach was taken, involving semi-structured interviews with internal stakeholders, enterprise customers and cybersecurity technology principals. The collected data were analysed using thematic coding and interpreted using PESTEL Analysis, Porter’s Five Forces, VRIO Analysis, SWOT Analysis, TOWS Matrix, Segmentation–Targeting-positioning (STP) and 7P Marketing Mix framework. The findings show the key challenge, not the lack of cybersecurity capability but how to convert operational capability into sustainable market differentiation and scalable execution. The study identifies major barriers to MSSP adoption as principal dependence, fractured commercial communication, inconsistent service packaging and poor operational coordination. To tackle these challenges, we propose four strategic directions to reinforce market positioning, enhance service integration, fortify proprietary capability development and introduce a more disciplined operating model to support the growth of recurring revenue.